Innovative Design, Manufacturing and Testing of Small Satellites - Madry, Scott (Astronautical Engineering,, 2018)
This book details key trends involving the recent formation of scores of companies that build and launch small satellites or provide key components for small satellite constellations. The applications and usage are quite diverse and include student experiments, serious scientific experimentation, and totally new types of commercial constellations, particularly in telecommunications and remote sensing. The explosive growth in the design, manufacturing, and launch of small satellites is one of the most dynamic aspects in the area of space exploration and exploitation today. New commercial space companies such as Planet Labs, Sky Box, OneWeb, and LeoSat are now building and launching thousands of small satellites and cubesats into orbit. Small companies and big aerospace companies alike are getting into this exciting and interesting new business. This is a practical guide that provides advice to students, researchers, LEO satellite companies, and regulators wrestling with some of the new challenges that small satellites present as more and more companies and countries around the world enter the new small satellite arena.